Analysis The Implementation of Science Process Skills (SPS) Assessment in Chemistry Learning in Indonesia: A Systematic Literature Review - Ovilia, Ghea; Sakina, Nifela; Nurlatifah, Nurlatifah; Nahadi, Nahadi (Hydrogen: Jurnal Kependidikan Kimia, 2024)
The assessment of science process skills (SPS) in chemistry learning is important because it allows teachers to evaluate how far students are able to apply science process skills in chemistry. This research is a Systematic Literature Review using PRISMA (The Preferred Reporting Items for Systematic Reviews and Meta-Analysis). The aims of this research is to understand the implementation of science process skills assessment in chemistry learning in Indonesia. The result shows that the implementation of SPS assessment in chemistry learning in Indonesia has been suitable with the purposes and principles of SPS assessment, however some indicators of SPS need improvement. The implementation of SPS assessment in chemistry learning should be integrated through contextual learning that involves students actively.